The Use of Creative Teaching Materials by Pre-Service Teachers Based on Canva for Education: A Literature Review (2016-2025) - Tiara Dwi Saiva; Yasfi Ismayani; Salman Hafizin (Indonesian Journal of Innovation and Educational Technology, 2026)
This study aims to systematically review the use of creative teaching materials developed by pre-service teachers using Canva for Education in enhancing the quality of learning. The urgency of this research is based on the rapid development of digital technology in education, which requires prospective teachers to possess both pedagogical competence and digital literacy skills. This study employs a qualitative approach through a literature review method by analyzing relevant national and international journal articles published between 2016 and 2025. The research procedures include identification of sources, selection based on inclusion criteria, critical analysis, and synthesis of findings. The results indicate that Canva for Education plays a significant role in supporting the development of creative and visually engaging teaching materials, improving instructional design skills, and increasing student motivation and engagement in learning. In addition, the use of Canva contributes to enhancing the professional readiness of pre-service teachers in integrating technology into classroom practices. However, several limitations were identified, including limited technological skills and access constraints. In conclusion, Canva for Education is an effective digital tool that supports innovative teaching practices and should be integrated into teacher education programs. Further studies are recommended to explore its implementation through empirical research in real classroom settings.